Maternal exposure to bisphenol A and anogenital distance throughout infancy: A longitudinal study from Shanghai, China. (December 2018) - Sun, Xiaowei; Li, Dekun; Liang, Hong; Miao, Maohua; Song, Xiuxia; Wang, Ziliang; Zhou, Zhijun; Yuan, Wei
Abstract: Background: Bisphenol A (BPA) is one of the most common endocrine-disrupting compounds (EDCs) with a ubiquitous presence. Both animal and human studies have reported the association between maternal exposure to BPA and anogenital distance (AGD) in offspring. However, the results are conflicting and the longitudinal effect is unknown. We aimed to examine the effect of maternal exposure to BPA on AGD in offspring in a longitudinal birth cohort from birth to 1 year of age. Methods: BPA was assayed using urine samples collected at 12–16 gestational weeks from 982 pregnant participants who later delivered infants. Infants' AGDs (AGDap [anus-penis] and AGDas [anus-scrotum] for boys, AGDac [anus-clitoris] and AGDaf [anus-fourchette] for girls) were measured at birth, and at 6 and 12 months of age. Multiple linear regression analysis was conducted to examine the associations between maternal exposure to BPA and offspring's AGDs. Then generalized estimating equation (GEE) model was applied to make use of the repeated measurements of AGDs and examine the overall effect of maternal exposure to BPA. Results: Compared to boys with undetected maternal BPA, those with detected BPA were more likely to have shorter AGDap and AGDas at 6 and 12 months. However, the differences were statistically significant for AGDap and AGDas only at 12 months (2.87 and 4.12 mm shorter, respectively). In GEE models, similar patterns were observed. Boys in the higher quartiles were more likely to have shorter AGDap and AGDas than those in the first quartile. However, statistically significant differences were only observed in boys in the third quartile. For girls, these associations were not observed regardless of the timing of measurements (at birth, 6 months and 12 months). Conclusions: Maternal exposure to BPA was associated with shortened AGDap and AGDas in boys at age 12 months but not in girls, which suggests a gender specific effect of BPA exposure on offspring's development. Highlights: Maternal exposure to BPA may have adverse effect on offspring's reproductive health as indicated by shortened AGD. For boys, maternal exposure to BPA was associated with shortened AGDs at 12 months. For girls, these associations were not observed regardless of the timing of measurements. Our findings suggest a gender specific effect of maternal exposure to BPA on offspring's development.